In time of plague : the Basotho and the rinderpest, 1896-8 - Phoofolo, Pule (Rhodes University, Faculty of Humanities, Department of History, 2000)
Rinderpest, the most dreaded bovine plague, struck the cattle of the BaSotho in British Basutoland early in 1897. By December the murrain had spent itself, having reduced the cattle population by half As it did so, the rinderpest claimed the primary historical significance of an epidemic. By sharpening behaviour and illuminating latent or developing tendencies, the rinderpest helped to reveal the nooks and crannies of contemporary historical processes that would have otherwise eluded historical visibility. This thesis brings out the complexities and ambiguities surrounding the epidemic. It uses the crisis occasioned by the panzootic in its multifaceted manifestations as a prism through which we might view the complex aspects of contemporary historical processes. It goes beyond the narrow limits of the crisis itself to discerning the broader and wider historical patterns that the rinderpest helped to highlight.
Keywords: Rinderpest -- Lesotho -- History; Epidemics -- Africa -- History; Livestock -- Diseases -- Africa; Sotho (African people) -- Social life and customs; Lesotho -- History